A High Order Method for Determining the Edges in the Gradient of a Function (Communications in Computational Physics, 2018)
Detection of edges in piecewise smooth functions is important in many applications. Higher order reconstruction algorithms in image processing and post processing of numerical solutions to partial differential equations require the identificationof smooth domains, creating the need for algorithms that will accurately identify discontinuities in a given function as well as those in its gradient. This work expands theuse of the polynomial annihilation edge detector, (Archibald, Gelb and Yoon, 2005), tolocate discontinuities in the gradient given irregularly sampled point values of a continuous function. The idea is to preprocess the given data by calculating the derivative,and then to use the polynomial annihilation edge detector to locate the jumps in thederivative. We compare our results to other recently developed methods.